2017
DOI: 10.1155/2017/1565602
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Youth Violence in Kumasi: Does Community Socialization Matter? A Cross-Sectional Study

Abstract: Violence by young people is one of the most visible forms of social disorder in urban settlements. This study assesses the causes and consequences of youth violence in the Kumasi metropolis. The study design was a nonexperimental cross-sectional survey. A mixed method approach facilitated the random sampling of 71 young people in the Kumasi metropolis through a stratified procedure between December 2014 and November 2015. Ten (10) participants were purposively selected and enrolled in a focus group discussion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…On the predictive potentials of respondents' employment status on the likelihood of victimisation within the neighbourhoods of the Ghanaian urban space, the odds of a person or a family member being a victim of crime is 0.717 times less likely for someone who is employed than for the unemployed. This finding confirms similar studies in Ghana (Warner, 2011;Barnie, et al, 2017) that the most likely victims of crime are the unemployed youth who form a significant proportion of Ghana's population. Similarly, Baah-Boateng (2015) indicates that 7 in every 10 youth are unemployed in Ghana.…”
Section: Characteristics Of Victims Of Crime In Urban Ghanasupporting
confidence: 91%
“…On the predictive potentials of respondents' employment status on the likelihood of victimisation within the neighbourhoods of the Ghanaian urban space, the odds of a person or a family member being a victim of crime is 0.717 times less likely for someone who is employed than for the unemployed. This finding confirms similar studies in Ghana (Warner, 2011;Barnie, et al, 2017) that the most likely victims of crime are the unemployed youth who form a significant proportion of Ghana's population. Similarly, Baah-Boateng (2015) indicates that 7 in every 10 youth are unemployed in Ghana.…”
Section: Characteristics Of Victims Of Crime In Urban Ghanasupporting
confidence: 91%
“…Other studies reported a lower prevalence of physical violence of 33.3% in Oyo State, [17] 28.0% in Ondo State, [18] but higher proportions (78.0%) [15] were reported in Rivers State, all within Nigeria and 54.9% in Ghana. [31] The most common pattern of bullying in this study was hitting, shoving or kicking in 29.5% of cases, followed by bullying via sexual gestures and jokes. In contrast, a study in Rivers State reported verbal aggression in 48.0% of respondents and physical attack in 20.8%.…”
Section: Discussionmentioning
confidence: 62%
“…The use of ATODs usually begins during adolescence, often for recreational purposes [6], but other motivations for use exist including coping motives in order to deal with social or mental health problems [18] or daily living for those in difficult circumstances on the streets or in conflict areas [19,20]. Multiple factors influence adolescent ATOD initiation, and prevention efforts have predominantly been rooted in a risk reduction/protection enhancement model [21].…”
Section: R Isk a N D Protec Ti V E Fac Tor S For Su Bsta Nce Usementioning
confidence: 99%